PERBEDAAN DAYA TAHAN NON SPESIFIK LIMA SPESIES IKAN AIR TAWAR TERHADAP INFEKSI Aeromonashydrophila - H. Syakuri; Triyanto Triyanto; K. H. Nitimulyo (Jurnal Perikanan Universitas Gadjah Mada, 2003)
Fish naturally has a non-specific defense against several pathogens. The non-specific defense is anatomical and physiological function that varies according to genetical and environmental factor. The differences of non-specific defense against Aeromonas hydrophila infection were studied in blackfinpacu (Colossoma macropomum), gourami (Osphronemus goramy), common crap (Cyprinus carpio), African catfish (Clarias gariepinus), and red nile tilapia (Orochromis sp.). This study also examined the differences on several parameters of non-specific defense, including differentiation anc number of leucocytes, serum total, titer of antibody, and antibacterial activity of skin mucus.The fishes were intramuscularly infected at the media lethal doses for common carp (7,4 x 108cfu/fish). Pathological changes, survival rate, and mean time to death were observed every day. The observation of non-specific defense parameters were carried out prior and at seven day after infection.The results showed thahblackfinpacu was the most resistant species against A. hydrophila infection. African catfish and red nile tilapia were most resistant than gourami and common carp. The antibody titer and percentage of thrombocytes were the causative factor for the difference of the resistence against A. hydrophila. The five fish species also showed differences on leucocytes number, monocytes and eosinophiles percentage, and serum total, but they did not showed the differences of neutrophile percentage. The skin mucus of all fish species did not exhibited antibacterial activity against A. hydrophila. This study also found increase in antibody titer and leucocytes number after A. hydrophila infection.